Peningkatan Pengetahuan Regulasi Emosi Melalui Psikoedukasi Kesehatan Mental di Majelis Taklim Nurul Iman - Alda Okti Ramadini; Ghina Ashilah; Artiarini Puspita Arwan (Yayasan Daarul Huda Kruengmane, 2025)
Mental health is a crucial aspect in determining an individual’s overall well-being. In the context of Indonesian society, mental health issues are still often considered taboo, as they are perceived as a sign of weak faith or lack of spirituality. In fact, maintaining a balance between mental health and spirituality plays a central role in creating a harmonious and empowered life. This Macro Professional Practice activity aims to increase knowledge of emotional regulation through mental health psychoeducation based on Islamic values at Majelis Taklim Nurul Iman, Mangrih Hamlet, Mojopuro Village, Wonogiri Regency. The method used is an educative-religious approach consisting of initial observation, interactive lectures, group reflection, Islamic relaxation practices, and participatory evaluation. The participants were 35 housewives who are active members of the Majelis Taklim and regularly attend religious study sessions. The results of the activity showed an improvement in participants’ understanding of mental health and emotional regulation concepts. Participants began to recognize that emotions such as anger, sadness, and anxiety are natural, as long as they are managed adaptively. Through spiritual practices such as dzikr (remembrance of Allah), istighfar (seeking forgiveness), and patience, participants were able to calm themselves and achieve inner peace. This activity also strengthened the role of Majelis Taklim as a means of spiritual and emotional empowerment for the community. Therefore, psychoeducation based on Islamic values proved effective in building a balance between psychological and spiritual aspects, as well as enhancing community mental resilience.